Defining genital tract cytokine signatures of sexually transmitted infections and bacterial vaginosis in women at high risk of HIV infection: a cross-sectional study. (8th August 2014) - Masson, Lindi; Mlisana, Koleka; Little, Francesca; Werner, Lise; Mkhize, Nonhlanhla N; Ronacher, Katharina; Gamieldien, Hoyam; Williamson, Carolyn; Mckinnon, Lyle R; Walzl, Gerhard; Abdool Karim, Quarraisha; Abdool Karim, Salim S; et al.
Abstract : Objectives: Sexually transmitted infections (STI) and bacterial vaginosis (BV) cause female genital tract inflammation. This inflammation, which is often present in the absence of symptoms, is associated with increased susceptibility to HIV infection. We aimed to evaluate genital cytokine profiles and the degree of inflammation associated with common STIs and BV. Methods: HIV-uninfected women (n=227) were screened for BV, Chlamydia trachomatis, Neisseria gonorrhoeae, Herpes simplex virus type 2 (HSV-2), and Trichomonas vaginalis . Concentrations of 42 cytokines in cervicovaginal lavages and 13 cytokines in plasma were measured using Luminex. Changes in cytokine profiles were evaluated using Mann–Whitney U test, logistic regression and factor analysis. p Values were adjusted for multiple comparisons using a false discovery rate step-down procedure. Results: Women with chlamydia or gonorrhoea had the highest genital cytokine concentrations, with 17/42 and 14/42 cytokines upregulated compared with women with no infection, respectively. BV was associated with elevated proinflammatory cytokine concentrations, but lower chemokine and haematopoietic cytokine concentrations. HSV-2 reactivation was associated with lower levels of inflammation, while trichomoniasis did not cause significant differences in genital cytokine concentrations. Genital infections did not influence plasma cytokine concentrations. Although certain STIs, in particular chlamydia and gonorrhoea, were associated with high genital cytokine concentrations, only 19% of women with an STI/BV had clinical signs. Conclusions: Chlamydia was associated with the highest genital cytokine levels, followed by gonorrhoea, HSV-2, trichomoniasis, and BV. In regions where HIV is prevalent and STIs are managed syndromically, better STI/BV screening is urgently needed, as certain infections were found to be highly inflammatory.